Jurnalisme Investigasi dalam Film Dokumenter The End Game - Cita Inggil Megawati; Agus Sriyanto (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
Watchdoc Documentary as one of the alternative media in Indonesia, often shows the results of journalistick work in a documentary film.one of them is The EndGame documentary film which raises issues about the current KPK situation. Watchdoc courage in covering the issue in depth caused controversy in various circles. That’s what makes me interested in knowing the description of investigative journalism that implemented in the film. This study uses a qualitative descriptive approach by analyzing using the theory of eight elements of investigative journalism and four characteristics of investigative journalism by Santana (2003). From the results of this study, shows that Watchdoc’s coverage of the KPK issue has fullfilled all the characteristics and elements of investigative journalism. However, in its search Watchdoc does not emphasize the principle of cover both side or search for the opposite point of view. Watchdoc doesn’t present sources from institutional representative, Watchdoc only uses open statements from various press conference and news snippets that have been published. In conclusion, the documentary film focuses more on how and why it happened, not revealing what and who is the mastermind behind the issue. So, overall the results are still not clear enough to be called as a perfect investigative journalism, but rather lead to in-depth reporting with an advocacy jornalism perspective.